STATINS INHIBITS GROWTH AND METASTASIS OF MELANOMA THROUGH MIR-126/MMP-9 - Nasser, Rasha (An-Najah National University, 2024)
Background: Melanoma is the deadliest type of skin cancer, with morbidity and mortality rates increasing globally. Melanoma has an elevated metastatic potential, leading to limited response to the available treatments in addition to poor prognosis. The transcription factor (NF-κB) for nuclear factor kappa B has been up-regulated in melanoma cases. Simvastatin has anticancer properties that can act as a repurposed drug for treating melanoma. Recognizing the signaling pathway and the anti-tumor properties of simvastatin is essential in discovering new kinds of tumors that might be intended by simvastatin. MicroRNA-126 is a significant microRNA family member; recent studies demonstrate its role in cancer as a new tumor suppressor gene because it can stop cancer cells from growing, migrating, and invading by suppressing important oncogenes like matrix metallopeptidase 9 (MMP9). Here, we inspected how simvastatin can affect melanoma growth, tumor cell migration, and angiogenesis. Mechanically, Simvastatin blocks the transcription factor NF-κB, which up-regulates MIR-126 and, therefore, down-regulates the expression of MMP9 as an oncogene of melanoma cancer responsible for cell proliferation, migration, and angiogenesis. Aims: Eliminating melanoma from our lives is our objective. The only way to accomplish this is through study, and it is pretty bold and huge. We propose that, rather than finding a new drug, it would be better to use an existing one to prevent growth and metastasis so that we can investigate the impact of statin drug on melanoma growth and metastasis using an innovative approach. This goal is supported by our unique research technique, which describes how we use the newest ideas to advance the discovery of a new treatment for melanoma. Methods: we use Simvastatin to block the transcription factor NF-κB, which then regulates the expression of MIR-126. Therefore, this micro-RNA inhibits the expression of MMP9 as an oncogene of melanoma cancer, responsible for cell proliferation, migration, angiogenesis, and metastasis. Results: The results of the study demonstrate that simvastatin, via inhibiting the transcription factor NFκB; can influence the growth and spread of melanoma cancer at even low concentrations (5µM). In conclusion: Through downregulation of the transcription factor NFκB, which restores the production of miR-126 that targets the MMP-9 mRNA, simvastatin possesses anti-proliferative characteristics that limit the growth and metastasis of the B16F10 melanoma cell line dependent on dosage and time approach.
الستاتينات تمنع نمو ورم خبيث في سرطان الجلد من خلال MIR-126/MMP-9